2021
DOI: 10.1111/obr.13298
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise consequences on memory in obesity: A systematic review

Abstract: Summary Obesity is associated with changes in memory. Thus, the aim of this systematic review was to investigate the physical exercise consequences on memory in obesity. A search was carried out in the PubMed, Lilacs, and Scielo databases with the following descriptors: “physical exercise,” “memory,” and “obesity.” A total of 16 studies were analyzed in this review. Low, moderate, and high intensity exercise training showed positive effects on memory in patients with obesity (100%). The animal models of obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 59 publications
(199 reference statements)
0
9
0
Order By: Relevance
“…Studies examining cognitive function in overweight and obese individuals have reported impairments in several cognitive domains including attention (Fergenbaum et al 2009), visuospatial function (Boeka and Lokken 2008), verbal memory (Cournot et al 2006), visual memory (Boeka and Lokken 2008), working memory (Coppin et al 2008), and executive function (conceptualization, inhibition) (Fagundo et al 2012). Participating in regular endurance physical exercise is thought to lead to cognitive benefits (Cassilhas et al 2012;De Sousa et al 2021c). The main findings in our study indicate that MICT and HIIT enhance, posterior to 8 weeks of the physical exercise protocol, serum BDNF levels, and improve the cognitive function of middle-aged overweight men (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining cognitive function in overweight and obese individuals have reported impairments in several cognitive domains including attention (Fergenbaum et al 2009), visuospatial function (Boeka and Lokken 2008), verbal memory (Cournot et al 2006), visual memory (Boeka and Lokken 2008), working memory (Coppin et al 2008), and executive function (conceptualization, inhibition) (Fagundo et al 2012). Participating in regular endurance physical exercise is thought to lead to cognitive benefits (Cassilhas et al 2012;De Sousa et al 2021c). The main findings in our study indicate that MICT and HIIT enhance, posterior to 8 weeks of the physical exercise protocol, serum BDNF levels, and improve the cognitive function of middle-aged overweight men (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“… 369 In addition, exercise enhances glucose homeostasis and protects against metabolic diseases such as obesity and diabetes. 370 Recently, investigators have demonstrated that exercise induces the phenotypic conversion of white adipocytes to thermogenic adipocytes through a range of mechanisms. 371 During exercise, increased plasma epinephrine stimulates lipolysis through acting cAMP, PKA, and phosphorylates adipose triglyceride lipase (ATGL).…”
Section: The Developmental Origin and Anatomical Location Of Thermoge...mentioning
confidence: 99%
“…In general, three methods have been proposed for the prevention and treatment of diabetes-induced AD-like symptoms, including diet therapy, medication, and exercise training [ 13 , 14 ]. Among them, exercise training has been emphasized because it does not have side effects, does not need special equipment, and is not expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, exercise training has been emphasized because it does not have side effects, does not need special equipment, and is not expensive. Added to these are the psychological advantages associated with exercise training [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%